The Impact of a Total Compensation System on Employee Retention Through Increased Job Satisfaction: An Analysis of Online Employee Reviews at Kopi Kenangan - Insani, Nazwa Asysara; Rоslyana, Nadia Saﬁra; Zalfadhiya, Nazwa; Zulﬁkri, Agung (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study attempts to examine the extent to which the total competency system influences a company's ability to retain its employees, by positioning job satisfaction as a variable mediating the relationship. The object of the study is centered on Kopi Kenangan, one of the most aggressive players in the Indonesian food and beverage (F&B) industry. The case study approach was conducted using secondary data sources, namely a collection of online reviews left by employees on the Glazdoor and Indeed platforms from 2021 to 2024. The analysis revealed that employee perceptions of both financial and non-financial compensation components remain below expectations, particularly regarding base salary, bonus schemes, and workload distribution. This inequality contributes to low job satisfaction, which ultimately increases the likelihood of employees leaving the company. This result is in line with the total reward framework developed by Milkovich, Newman & Gerhart (2020) and Herzberg's two-factor theory, and also provides a basis for recommendations for companies in the F&B sector to redesign their compensation policies in a more comprehensive and strategic manner.